Teenage crisis school for students who become pregnant before marriage. - Arini, Diana Putri (Universiti Sains Malaysia, 2014)
Getting pregnant among unmarried teenagers is an unwanted pregnancy. This is included in a juvenile delinquency, and in everyday life it can be categorized as a deviant behavior. The consequences that must be faced by the pregnant students are expulsion from school and early marriage.